Gene Effects and Hetfrosis for Some Quantitative Characters in Clusterbean - Arora, R N; Saini, M L; Paroda, R S (Annals of Arid Zone, 2016)
Studies on gene effects, heterosis and inbreeding depression for eleven quantitative characters in two crosses of clusterbean [Cyamopsis tetragonolaba (L.) Taub.] revealed that additive, dominance and additive x additive genetic components were predominant in Mills x Durgajay whereas HFG60 x Durgajay exhibited dominance x dominance gene effects for most of the traits. Both duplicate and complementary type of epistasis were involved in most of the characters in both the crosses. High heterosis and less inbreeding depression were observed for pods/plant and seed yield/plant in Mills x Durgajay.